Elasticsearch server. - Kuć, Rafał (Packt Pub., 2013)
In Detail ElasticSearch is an open source search server built on Apache Lucene. It was built to provide a scalable search solution with built-in support for near real-time search and multi-tenancy. Jumping into the world of ElasticSearch by setting up your own custom cluster, this book will show you how to create a fast, scalable, and flexible search solution. By learning the ins-and-outs of data indexing and analysis, "ElasticSearch Server" will start you on your journey to mastering the powerful capabilities of ElasticSearch. With practical chapters covering how to search data, extend your search, and go deep into cluster administration and search analysis, this book is perfect for those new and experienced with search servers. In "ElasticSearch Server" you will learn how to revolutionize your website or application with faster, more accurate, and flexible search functionality. Starting with chapters on setting up your own ElasticSearch cluster and searching and extending your search parameters you will quickly be able to create a fast, scalable, and completely custom search solution. Building on your knowledge further you will learn about ElasticSearch's query API and become confident using powerful filtering and faceting capabilities. You will develop practical knowledge on how to make use of ElasticSearch's near real-time capabilities and support for multi-tenancy. Your journey then concludes with chapters that help you monitor and tune your ElasticSearch cluster as well as advanced topics such as shard allocation, gateway configuration, and the discovery module. Approach This book is written in friendly, practical style with numerous hands-on examples and tutorials throughout. Who this book is for This book is written for developers who wish to leverage ElasticSearch to create a fast and flexible search solution. If you are looking to learn ElasticSearch or become more proficient then this book is for you. You do not need know anything about ElasticSeach, Java, or Apache Lucene in order to use this book, though basic knowledge about databases and queries is required.
Keywords: Application software.; Client/server computing -- Software.; elektronické knihy; electronic books